Gambaran Persepsi Perawat dalam Pendokumentasian Pemasangan Infus Berbasis Komputer di Rumah Sakit X di Depok - Sianturi, Sondang Ratnauli; Naibaho, Romasa (Universitas Muhammadiyah Magelang, 2020)
Documentation of the written nursing (paper-based documentation) is currently reported to be of very low quality and this also has an impact on public acceptance including other health professions on the professionalization of nursing. Computer-based nursing documentation is a combination of hospital computer systems and nursing documentation filled by nurses. The purpose of this study was to determine the description of the characteristics and perceptions of nurses in documenting computer-based infusion. The research method used is quantitative descriptive method. The sample in the study amounted to 150 respondents taken using total sampling. Data collection tools using questionnaires about the perception of nurses with a Likert scale. The results of the characteristic analysis showed that the frequency of female sex was 138 people (92%), the frequency of age was 21-40 years at the most 145 people (96.7%) and the frequency of education was Nursing Diploma 124 people (82.7%). Analysis of nurses' perceptions showed a good perception of 50% and a poor perception of 50%. The result showed that nurses need more information and supervision. Continuous evaluation and training are needed so that all nurses are expected to be exposed to computer-based documentation information and in need of reward and punishment for nurses in terms of computer-based documentation.